Correlation Between the Five Personality Dimensions and Creative Behaviours of Electrical and Electronics Teachers in Nigerian Technical Colleges - Raymond, Emmanuel; Uduafemhe, Maxwell Emmanuel; Alome, Sunday A.; Bamidele, & Oguma (Journal of Technical Education and Training, 2018)
This study determined the correlations between the five personality dimensions and the creative behaviours of electrical and electronics teachers in Nigerian Technical Colleges. Multiple prediction research design was adopted for the study. Purposive sampling technique was used to select 94 electrical and electronics teachers from a population of 137 persons teaching electrical and electronics trades in the 21 technical colleges in North-western Nigeria. The data for the study were collected using two instruments: Kaufman Domains of Creativity Scale which consists of 50 items in which participants rated themselves on a scale of 1 to 5 in comparison to other people in their age and experience, and Goldberg’s Big Five Inventory which is a 44 item, five point Likert scale type of; Strongly Disagree, Disagree, Neutral, Agree, and Strongly Agree. To account for socio-cultural differences, the instruments were subjected to a pilot study in Niger State, North-central Nigeria, and their reliability coefficients were found to be 0.86 and 0.83 respectively. The data were analysed using Pearson Product Moment Correlation and Multiple Regression. Results revealed that there is a correlation between the five personality dimensions when treated together and the creative behaviours of electrical and electronics teachers. Also, the personality dimensions treated together significantly correlate with the creative behaviours of the teachers. It was concluded that personality traits are important for creative behaviours of trade’s teachers. Hence, a reward and incentive systems should be put in place, for the encouragement of creativity among electrical and electronics teachers in technical colleges in Nigeria.